Safety and Efficacy of Topical Lotilaner Ophthalmic Solution 0.25% for the Treatment of Demodex Blepharitis: A Pilot Study - Roberto Gonzalez-Salinas; Elizabeth Yeu; Mark Holdbrook; Stephanie N. Baba; Juan Carlos Ceballos; Martha Massaro-Corredor; Claudia Corredor-Ortega; Nallely Ramos-Betancourt; Hugo Quiroz-Mercado (Journal of Ophthalmology)
Purpose. Evaluate safety and efficacy of topical lotilaner ophthalmic solution, 0.25% for the treatment of Demodex blepharitis. Patients and Methods. 15 patients with Demodex blepharitis, defined as >10 collarettes on the upper lid, lid margin erythema, and Demodex density of ≥1.5 mites/lash on microscopy, were treated bid for 28 days with lotilaner ophthalmic solution, 0.25%. Contact lens wear, artificial eyelashes, and lid structural abnormalities were among the exclusion criteria. No other antibacterial, antiparasitic, or anti-inflammatory treatment or lid hygiene products were permitted. Patients were assessed on Days 7, 14, 28, 60, and 90. Outcome measures were changes in collarette grade and mite density on Day 28. Adverse events and changes in intraocular pressure (IOP), corrected distance visual acuity (CDVA), and slit-lamp biomicroscopy were assessed. Results. Mean collarette grade (upper lids) improved from 3.07 ± 0.21 to 0.79 ± 0.19 on Day 28; the change was statistically significant for both upper and lower lids from Day 14 on. Mean mite density per lash decreased from 2.28 ± 0.16 at baseline to 0.14 ± 0.05 at Day 28 p<0.0001. Mite eradication (0 mites) was documented in 57.1% of eyes. The effects were durable through Day 90. There were no adverse events and little to no change in CDVA or IOP. The drop was well tolerated, with no discontinuations due to ocular irritation. Conclusion. Topical lotilaner ophthalmic solution, 0.25% for 4 weeks, showed promising efficacy for the treatment of Demodex blepharitis. This novel treatment appears to be safe and well tolerated. Randomized controlled studies are needed to confirm the results.